Immunotoxicity Testing Methods and Protocols - Dietert, Rodney R. (Methods in Molecular Biology™, Methods and Protocols, 2010)
Recent critical advances in the field of immunotoxicology have led to incredible contributions to basic science, including crucial improvements in human risk assessment. In Immunotoxicity Testing: Methods and Protocols, expert researchers explore these changes, providing the reader with current, lab-ready procedures, along with the corresponding background information that is necessary to identify effective testing approaches for chemicals and drugs. Among the first volumes to meld consideration of immunotoxicity testing strategies with a comprehensive presentation of detailed laboratory protocols, chapters include a description of the evolution of immunotoxicity testing, a look at the importance of immunotoxicity testing for health risk reduction, and ideas concerning the future of the field. Composed in the highly successful Methods in Molecular Biology(tm) series format, most chapters contain a brief introduction, step-by-step methods, a list of necessary materials, and a Notes section which shares tips from the experts on troubleshooting and avoiding known pitfalls. Comprehensive and innovative, Immunotoxicity Testing: Methods and Protocols is a critical, one-stop reference resource for the most important and commonly used laboratory protocols in immunotoxicology